Hydrogel material for genital organ plastic surgery
By crosslinking sodium alginate, gelatin, carboxymethyl chitosan with mesenchymal stem cell solution, and combining the self-assembly technology of zwitterionic copolymer and heparin calcium, a hydrogel material for genital plastic surgery was prepared, which solved the problem of The problems of poor mechanical properties of existing materials and long plastic surgery repair cycles have achieved efficient plastic surgery repair and antibacterial and anti-inflammatory effects.
Patent Information
- Application Number
- CN202411123152.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-08-15
AI Technical Summary
The mechanical properties of existing genital plastic surgery materials are poor, the plastic surgery and repair cycle is long, and there are problems such as poor customization and high price.
Sodium alginate, gelatin, carboxymethyl chitosan and mesenchymal stem cell solution were blended with calcium ion cross-linked and lyophilized, and self-assembly technology of zwitterionic copolymer, heparin calcium and tannin acid were prepared. A hydrogel material for genital plastic surgery.
It improves the mechanical properties of the material and the plastic surgery and repair effect, shortens the plastic surgery and repair cycle, has excellent antibacterial and anti-inflammatory effects, and reduces the cost of the material.
Smart Images

Figure BDA0004995628330000151 
Figure BDA0004995628330000161
Abstract
Description
Technical Field
[0001] The invention relates to a hydrogel material for genital plastic surgery and a preparation method thereof. The invention belongs to the field of biomedical materials. Background Art
[0002] The progress of reproductive plastic surgery technology is good news for some male friends with congenital genital defects, allowing them to regain confidence. For some patients with urogenital tract malformations, trauma, and penile malignant tumors, the current drug treatment effect is very limited. The main method is surgical prosthesis implantation, including skin flaps or cartilage combined with artificial prostheses to reconstruct the penis, etc. However, due to the lack of normal corpus cavernosum tissue, the recovery of the appearance and erectile function of the penis after surgery in most patients is still not optimistic. Therefore, the key to improving penile reconstruction surgery is to develop artificial synthetic materials that can replace natural corpus cavernosum. There are specific requirements for the structural characteristics, angiogenesis, and mechanical properties of the materials. It is necessary to meet the reticular tissue structure and special diastolic force of the corpus cavernosum, and it is also necessary to have abundant vascular sinus formation to truly achieve the recovery of penile erectile function.
[0003] Currently, commonly used materials are biocompatible materials such as silicone rubber, but due to differences in stiffness, poor affinity and other heterogeneous challenges, they can cause discomfort in the early stages of implantation and damage the remaining sponge and its function. In addition, the size of the prosthesis will also affect comfort and functionality. Current products have problems such as poor customization and high prices.
[0004] In addition, due to the complexity of the genital structure, the formation of fat cells, epithelial cells, and endothelial cells after the implantation of the material is slow, and the entire plastic surgery and repair cycle is too long, which seriously affects the treatment effect. Human mesenchymal stem cells are a type of cell that can self-renew and have multidirectional differentiation capabilities. They can differentiate into fat cells, bone cells, chondrocytes, etc., and can also differentiate into urothelial cells, vascular endothelial cells, etc. At the same time, they have paracrine capabilities and play a role in tissue repair and immune regulation. In recent years, mesenchymal stem cell-derived therapy has become one of the promising strategies for the treatment of neurodegenerative diseases.
[0005] Therefore, it is of great significance to develop an implant material and a preparation method thereof that has high compatibility, excellent compliance, and rapid repair. Summary of the invention
[0006] The purpose of the present invention is to solve the problems of poor mechanical properties and long plastic surgery repair cycle of genital plastic surgery materials in the prior art, and to provide a new method for preparing a hydrogel material for genital plastic surgery. Considering the excellent properties of sodium alginate, gelatin, and carboxymethyl chitosan as biomaterials, they are used as the main raw materials, blended with mesenchymal stem cell solution, freeze-dried, cross-linked with calcium ions, and self-assembled to prepare; while solving the problem, it also has excellent antibacterial and anti-inflammatory effects. The technical solution adopted by the present invention to solve its technical problems is:
[0007] The present invention provides a method for preparing a zwitterionic copolymer, comprising the following steps:
[0008] S11, subjecting lactic acid, carboxylated catechol derivative and epoxy acrylate to a ring-opening reaction to obtain an intermediate product;
[0009] S12, subjecting the intermediate product and zwitterion to free radical polymerization to obtain a target product, namely a zwitterionic copolymer.
[0010] Further, the lactic acid, the carboxylated catechol derivative and the epoxy acrylate are added in a molar ratio of the total amount of carboxyl groups to the epoxy groups of 1:1; and,
[0011] The usage ratio of the lactic acid and the carboxylated catechol derivative is 0.3-0.5 mol: 0.5-0.7 mol.
[0012] Further, the ratio of the intermediate product to the zwitterion is 0.4-0.5 mol: 0.5-0.6 mol; and,
[0013] The zwitterion contains an acryloyloxy structure.
[0014] The present invention also provides a zwitterionic copolymer prepared by the above-mentioned preparation method.
[0015] Another object of the present invention is to provide a method for preparing a hydrogel material for genital plastic surgery, comprising the following steps:
[0016] S21, preparing the mixed solution and freeze-drying, i.e.
[0017] Add mesenchymal stem cell solution to the polymer base mixed solution, mix well and pour into a mold; freeze-dry;
[0018] S22, ionic cross-linking, i.e.
[0019] The substance obtained in step S21 is placed in a calcium chloride solution, allowed to stand for 30-40 minutes, and excess liquid is removed;
[0020] S23, self-assembly, i.e.
[0021] The material obtained in step S22 is placed in a zwitterionic copolymer solution, heparin calcium solution A, tannic acid solution, and heparin calcium solution B in sequence; wherein each process is allowed to stand for 40-60 minutes;
[0022] S24, freeze-dried, i.e.
[0023] The material obtained in step S23 is freeze-dried to obtain a hydrogel material for genital plastic surgery.
[0024] Furthermore, the polymer-based mixed solution is a mixture of sodium alginate solution, carboxymethyl chitosan solution and gelatin solution in a volume ratio of 1.0-2.0:1.0:1.0-2.0; and
[0025] The concentration of the sodium alginate solution is 0.02-0.05 g / mL;
[0026] The concentration of the carboxymethyl chitosan solution is 0.01-0.03 g / mL;
[0027] The concentration of the gelatin solution is 0.02-0.05 g / mL.
[0028] Furthermore, the solute sodium alginate of the sodium alginate solution is added by high molecular weight sodium alginate and low molecular weight sodium alginate in a mass ratio of 0.6-0.8:0.2-0.4; and
[0029] The number average molecular weight of the high molecular weight sodium alginate is 100-150 kDa;
[0030] The number average molecular weight of the low molecular weight sodium alginate is 5-10 kDa.
[0031] Furthermore, the volume ratio of the mesenchymal stem cell solution to the polymer-based mixed solution is 1.0:0.8-1.2;
[0032] The concentration of the mesenchymal stem cell solution is 10 9 -10 10 Pieces / mL.
[0033] Furthermore, the concentration of the calcium chloride solution is 0.01-0.03 g / mL.
[0034] Further, the concentration of the zwitterionic solution is 0.01-0.02 g / mL;
[0035] The concentration of the heparin calcium solution A is 0.005-0.01 g / mL;
[0036] The concentration of the tannic acid solution is 0.005-0.01 g / mL; and
[0037] The concentration of the heparin calcium solution B is 0.01-0.02 g / mL.
[0038] Beneficial effects of the present invention:
[0039] (1) The present invention provides a method for preparing a hydrogel material for genital plastic surgery, which uses sodium alginate, gelatin, and carboxymethyl chitosan as main raw materials, which are mixed with a mesenchymal stem cell solution and freeze-dried, and then calcium ion cross-linked, and zwitterionic copolymers, heparin calcium, tannic acid, and heparin calcium are self-assembled to prepare the hydrogel material. First, the hydrogel with sodium alginate as the main component and gelatin and carboxymethyl chitosan as the auxiliary components has excellent mechanical properties, antibacterial properties, and functions of promoting cell proliferation and differentiation; second, the sodium alginate structure is used in a high-low molecular weight structure, which has excellent flexibility while ensuring mechanical strength; third, the mesenchymal stem cell solution is blended and freeze-dried with sodium alginate, gelatin, and carboxymethyl chitosan solution, which helps the stem cell structure to remain intact in the pores of the hydrogel and maintain biological activity, thereby reducing the plastic surgery repair cycle; fourth, the zwitterionic copolymer can further improve the mechanical properties of the hydrogel on the one hand; on the other hand, it can improve the adsorption rate of heparin calcium and tannic acid, and has the functions of improving anti-inflammatory and antibacterial properties and preventing thrombosis; fifth, heparin calcium has excellent anti-thrombotic effects, is not easy to cause electrolyte disorders, and is adsorbed in the hydrogel at the same time, and has a long-lasting effect. Sixth, the tannic acid structure on the surface of the hydrogel has excellent cell adsorption and promotes healing.
[0040] (2) The present invention provides a hydrogel material for genital plastic surgery, which uses a self-made zwitterionic copolymer containing zwitterions, alcoholic hydroxyl groups, catechol, and ester structures. First, the zwitterionic copolymer has excellent biocompatibility and water solubility; second, the zwitterions can provide electrostatic adsorption between gelatin and carboxymethyl chitosan, and the alcoholic hydroxyl groups form hydrogen bonds with sodium alginate, gelatin, and carboxymethyl chitosan, thereby improving the mechanical properties; third, the catechol structure can form coordination with heparin calcium, and is similar to and compatible with the tannic acid structure, thereby improving the mechanical properties. DETAILED DESCRIPTION
[0041] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.
[0042] The purpose of the present invention is to develop a hydrogel material for genital plastic surgery that has excellent mechanical properties and can improve the effect of plastic surgery and repair. The idea of implementation is: combined with sodium alginate, it has excellent biocompatibility and biodegradability, and can be cross-linked with calcium ions to form a stable three-dimensional hydrogel; gelatin, as a hydrolysate of collagen, has good biocompatibility, biodegradability and low antigenicity, can promote cell proliferation and differentiation, help platelet aggregation, and has excellent mechanical properties; carboxymethyl chitosan has excellent biocompatibility and biodegradability, as well as good antibacterial and film-forming properties. It is used as the main raw material to load mesenchymal stem cells with high differentiation ability, promote their differentiation into genital tissues, and improve the effect of plastic surgery and repair; at the same time, it is supplemented by the synergistic effect of improving mechanical properties, cell adsorption, and antibacterial and anti-inflammatory structures. The theoretical basis for the realization is: first, sodium alginate is supplemented with two molecular weights to improve strength and toughness; then it is blended with gelatin and carboxymethyl chitosan; then it is mixed evenly with the mesenchymal stem cell solution, and after freeze-drying process, a preliminary cross-linking is formed to lock the stem cells and improve the efficacy; second, the preliminary cross-linked product formed above is placed in a calcium chloride ion solution to form a hydrogel with a cross-linked structure; third, the hydrogel surface contains exposed amino and hydroxyl structures that hydrogen bond with the anions and cations and hydroxyls in the zwitterionic copolymer; then it is placed in heparin calcium to coordinate with the zwitterionic copolymer; then it is placed in tannic acid, and the calcium ions in the heparin calcium are coordinated with the tannic acid; finally, it is placed in heparin calcium to form a final product enriched with heparin calcium. After freeze-drying preliminary cross-linking, calcium ion multi-step cross-linking, and freeze-drying process, the mechanical properties can be effectively improved; at the same time, chitosan, zwitterionic copolymers, heparin calcium, tannic acid and other substances work synergistically with each other, have excellent anti-thrombotic and antibacterial functions, can promote rapid cell differentiation, and improve plastic repair effects. The embodiments of the present invention are as follows:
[0043] The embodiment of the present invention provides a method for preparing a zwitterionic copolymer, comprising the following steps:
[0044] S11, protect from light, add lactic acid, carboxylated catechol derivative, epoxy acrylate, inhibitor and tetrabutylammonium bromide to tetrahydrofuran, heat and reflux for 18-24 hours; cool to room temperature, distill under reduced pressure, take the concentrate and vacuum dry it at 40°C for 12 hours to obtain an intermediate product.
[0045] The lactic acid, carboxylated catechol derivative and epoxy acrylate are added in a molar ratio of the total amount of carboxyl groups to the epoxy groups of 1:1; and
[0046] The lactic acid and carboxylated catechol derivative are used in a ratio of 0.3-0.5 mol to 0.5-0.7 mol;
[0047] The usage ratio of the epoxy acrylate, tetrabutylammonium bromide and tetrahydrofuran is 0.1 mol: 0.02 mol: 100 mL;
[0048] The amount of the polymerization inhibitor used is 0.2 wt % of the epoxy acrylate; and the polymerization inhibitor in the following embodiments of the present invention is p-hydroxyanisole.
[0049] The carboxylated catechol derivatives may be protocatechuic acid, protocatechuic acid, gallic acid, dihydrocaffeic acid, danshensu, etc., and gallic acid is preferred.
[0050] The epoxy acrylate may be glycidyl methacrylate or (glycidyloxy)ethyl methacrylate, etc., and preferably glycidyl methacrylate.
[0051] S12, adding the intermediate product, zwitterion and photoinitiator to N,N-dimethylformamide, irradiating under UV lamp for 10-50 min, removing the UV lamp, performing vacuum distillation, adding methanol to the concentrate to produce a precipitate, filtering, taking the precipitate, and vacuum drying at 60°C for 8 h to obtain a zwitterionic copolymer.
[0052] The usage ratio of the intermediate product, the zwitterion and N,N-dimethylformamide is 0.4-0.5 mol: 0.5-0.6 mol: 500 mL.
[0053] The zwitterion is an acryloyloxy structure, which may be 2-methacryloyloxyethyl phosphorylcholine, methacryloylethyl sulfobetaine, or the like.
[0054] The amount of the photoinitiator is 1-5wt% of the total mass of the reactants;
[0055] The photoinitiator is a commonly used photoinitiator, which may be photoinitiator 1173, photoinitiator 184, photoinitiator 2959, photoinitiator 369 or photoinitiator TPO, etc.; and the photoinitiator described in the following embodiments of the present invention is photoinitiator 1173.
[0056] The UV light intensity is 200-600mW / cm 2 .
[0057] The embodiment of the present invention also provides a method for preparing a hydrogel material for genital plastic surgery, comprising the following steps:
[0058] S21, preparing the mixed solution and freeze-drying, i.e.
[0059] The mesenchymal stem cell solution was added to the polymer-based mixed solution, mixed evenly and poured into a mold; and freeze-dried at -20°C for 24 hours.
[0060] The preparation method of the polymer-based mixed liquid is: prepare sodium alginate solution, carboxymethyl chitosan solution and gelatin solution respectively for standby use; the preparation method of sodium alginate comprises: dissolving sodium alginate in deionized water containing a magnetic rotor, stirring at room temperature for 2 hours, and filtering with 0.6 μm and 0.3 μm microporous filter membranes to sterile, to obtain a solution with a concentration of 0.02-0.05 g / mL; the preparation method of carboxymethyl chitosan comprises: dissolving carboxymethyl chitosan in deionized water, stirring until there are no particles, and filtering with 0.6 μm and 0.3 μm microporous filter membranes to sterile, to obtain a solution with a concentration of 0.02-0.05 g / mL; , 0.3μm microporous filter membrane to sterile, to obtain a solution with a concentration of 0.01-0.03g / mL; the preparation method of gelatin comprises: dissolving gelatin in deionized water, heating to 50°C in a water bath, stirring until completely dissolved, and filtering with 0.6μm and 0.3μm microporous filter membranes in sequence to sterile, to obtain a solution with a concentration of 0.02-0.05g / mL; mixing sodium alginate, carboxymethyl chitosan and gelatin solution in a volume ratio of 1.0-2.0:1.0:1.0-2.0 to obtain a polymer-based mixed solution;
[0061] The solute sodium alginate of the sodium alginate solution is prepared by adding high molecular weight sodium alginate and low molecular weight sodium alginate in a mass ratio of 0.6-0.8:0.2-0.4; and
[0062] The number average molecular weight of the high molecular weight sodium alginate is 100-150 kDa; it can be 100 kDa, 110 kDa, 120 kDa, 130 kDa, 140 kDa, 150 kDa, or a range consisting of any two values;
[0063] The number average molecular weight of the low molecular weight sodium alginate is 5-10 kDa; it can be 5 kDa, 6 kDa, 7 kDa, 8 kDa, 9 kDa, 10 kDa, or a range consisting of any two values.
[0064] The volume ratio of the mesenchymal stem cell solution to the polymer base mixed solution is 1.0:0.8-1.2;
[0065] The concentration of the mesenchymal stem cell solution is 10 9 -10 10 Pieces / mL;
[0066] The mesenchymal stem cells can be bone marrow-derived mesenchymal stem cells, umbilical cord mesenchymal stem cells, placental mesenchymal stem cells, urine-derived mesenchymal stem cells, etc.; and, the mesenchymal stem cells described in the following embodiments of the present invention are umbilical cord mesenchymal stem cells.
[0067] The mesenchymal stem cell serum-free culture medium used in the present invention was purchased from Shanghai Xiaopeng Biotechnology Co., Ltd., and the trade name is: Human Mesenchymal Stem Cell Serum-Free Basic Culture Medium (Israel Biological Industries, Product No.: 05-200-1A). It is a clinical-grade mesenchymal stem cell culture medium, serum-free, free of xenobiotic components, and can maintain the typical characteristics of mesenchymal stem cells. It has obtained the U.S. FDA clinical registration number (DMFNO: 29469).
[0068] The preparation method of the mesenchymal stem cell solution described in the following embodiments of the present invention is:
[0069] (1) Take 200 mL of sterile fat from the patient's abdomen removed or liposuctioned in vitro. After the fat tissue is fully separated and minced, wash it three times with a 0.25% chloramphenicol solution, and repeatedly wash it with a 37°C phosphate buffer until the washing liquid under the fat layer turns light red after standing. The fat tissue is digested with 0.1% type I collagenase (Sigma-Aldrich Co. LLC., MO, USA) for 30 min-1 h until it becomes chylous, and centrifuge at 1200g for 10 min at 37°C to collect the stromal vascular fraction precipitate. The precipitate is resuspended in clinical-grade mesenchymal stem cell serum-free culture medium and filtered through a 100 μm nylon filter. Then, 10 mL per dish is injected into 10 cm culture dishes using a pipette. The culture dishes are cultured in an incubator at 37°C containing 5% humidified carbon dioxide by volume;
[0070] (2) Subculture of mesenchymal stem cells: The human adipose-derived mesenchymal stem cells of (1) were cultured in a clinical-grade mesenchymal stem cell serum-free culture medium, and the culture medium was replaced every two days. When the cell fusion reached 80-90%, they were digested with 0.25% trypsin by mass percentage and subcultured at a ratio of 1:3. The adipose-derived mesenchymal stem cells of the P4 generation were identified for osteogenic and adipogenic differentiation, and surface antigens (CD29, CD44, CD73, CD105, CD34, CD45) were identified before use;
[0071] (3) Quantification: Mesenchymal stem cells were diluted 1000 times in phosphate buffer and automatically analyzed in the Nanosight instrument based on Brownian motion and diffusion coefficient. The parameters were set as follows: temperature 26.0±0.1°C, viscosity 0.870±0.002 cP, 25 frames / s, and test time 60 s.
[0072] S22, ionic cross-linking, i.e.
[0073] The substance obtained in step S21 is placed in a calcium chloride solution, allowed to stand for 30-40 minutes, and excess liquid is removed;
[0074] The preparation method of the calcium chloride solution comprises: dissolving anhydrous calcium chloride powder in deionized water, stirring until no particles are present, filtering with 0.6 μm and 0.3 μm microporous filter membranes in sequence until sterile, and obtaining a solution with a concentration of 0.01-0.03 g / mL.
[0075] S23, self-assembly, i.e.
[0076] The material obtained in step S22 is placed in the zwitterionic copolymer solution, heparin calcium solution A, tannic acid solution, and heparin calcium solution B in sequence; wherein each process is allowed to stand for 40-60 minutes.
[0077] The concentration of the zwitterionic solution is 0.01-0.02 g / mL;
[0078] The concentration of the heparin calcium solution A is 0.005-0.01 g / mL;
[0079] The concentration of the tannic acid solution is 0.005-0.01 g / mL; and
[0080] The concentration of the heparin calcium solution B is 0.01-0.02 g / mL.
[0081] S24, freeze-dried, i.e.
[0082] The substance obtained in step S23 is freeze-dried at -20°C for 24 hours to obtain a hydrogel material for genital plastic surgery.
[0083] In the preparation method of the hydrogel material for genital plastic surgery provided by the embodiment of the present invention, sodium alginate, carboxymethyl chitosan, and gelatin solution are first mixed with a mesenchymal stem cell solution, and then freeze-dried and cross-linked with calcium ions, which can fix the cells in the hydrogel to the greatest extent and effectively reduce the plastic surgery repair cycle; in addition, the compound use of calcium chloride and heparin calcium can reduce material costs while achieving high-efficiency anti-thrombotic performance, which is conducive to its popularization and use.
[0084] In order to further understand the present invention, a hydrogel material for genital plastic surgery provided by the present invention is described in detail below in conjunction with specific embodiments, and the protection scope of the present invention is not limited by the following embodiments.
[0085] Example 1
[0086] A method for preparing a zwitterionic copolymer comprises the following steps:
[0087] S11, protect from light, add lactic acid, gallic acid, glycidyl methacrylate, inhibitor and tetrabutylammonium bromide to tetrahydrofuran, heat and reflux for 20 hours; cool to room temperature, distill under reduced pressure, take the concentrate and place it under vacuum at 40°C for 12 hours to obtain an intermediate product.
[0088] The lactic acid, gallic acid and glycidyl methacrylate are added in a molar ratio of 1:1 between the total amount of carboxyl groups and the epoxy groups; and
[0089] The dosage ratio of lactic acid to gallic acid is 0.4 mol:0.6 mol;
[0090] The usage ratio of glycidyl methacrylate, tetrabutylammonium bromide and tetrahydrofuran is 0.1 mol: 0.02 mol: 100 mL;
[0091] The dosage of the polymerization inhibitor is 0.2 wt % of glycidyl methacrylate.
[0092] Its infrared data are as follows: 3495cm -1 : -OH broad peak exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1735cm -1 :-C=O exists; 1606cm -1 、811cm -1 :-C=C- exists; 1265cm -1 、893cm -1 、825cm -1 : Epoxy group does not exist.
[0093] S12, adding the intermediate product, 2-methacryloyloxyethyl phosphorylcholine, and photoinitiator 1173 to N,N-dimethylformamide, irradiating under UV lamp for 30 minutes, removing the UV lamp, performing vacuum distillation, adding methanol to the concentrate to produce a precipitate, filtering, taking the precipitate, and vacuum drying at 60°C for 8 hours to obtain a zwitterionic copolymer
[0094] The usage ratio of the intermediate product, 2-methacryloyloxyethyl phosphorylcholine and N,N-dimethylformamide is 0.45 mol: 0.55 mol: 500 mL.
[0095] The amount of the photoinitiator 1173 is 3wt% of the total mass of the reactants;
[0096] The UV light intensity is 400mW / cm 2 .
[0097] Its infrared data are as follows: 3495cm -1 : -OH broad peak exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1735cm -1 :-C=O exists; 1606cm -1 、811cm -1 :-C=C- does not exist; 1187cm -1 :-P=O exists.
[0098] A method for preparing a hydrogel material for genital plastic surgery, comprising the following steps:
[0099] S21, preparing the mixed solution and freeze-drying, i.e.
[0100] The mesenchymal stem cell solution was added to the polymer-based mixed solution, mixed evenly and poured into a mold; and freeze-dried at -20°C for 24 hours.
[0101] The polymer-based mixed solution is: a solution with a sodium alginate solution concentration of 0.04 g / mL; a solution with a carboxymethyl chitosan solution concentration of 0.02 g / mL; and a solution with a gelatin solution concentration of 0.04 g / mL; sodium alginate, carboxymethyl chitosan, and gelatin solution are mixed at a volume ratio of 1.5:1.0:1.5 to obtain a polymer-based mixed solution;
[0102] The solute sodium alginate of the sodium alginate solution is prepared by adding high molecular weight sodium alginate and low molecular weight sodium alginate in a mass ratio of 0.7:0.3; and
[0103] The number average molecular weight of the high molecular weight sodium alginate is 130 kDa;
[0104] The number average molecular weight of the low molecular weight sodium alginate is 8 kDa;
[0105] The volume ratio of the mesenchymal stem cell solution to the polymer base mixed solution is 1.0:1.0;
[0106] The concentration of the mesenchymal stem cell solution is 5×10 9 Pieces / mL.
[0107] S22, ionic cross-linking, i.e.
[0108] The substance obtained in step S21 is placed in a calcium chloride solution, allowed to stand for 30 minutes, and excess liquid is removed;
[0109] The concentration of the calcium chloride solution is 0.02 g / mL.
[0110] Its infrared data is as follows: 3486cm-1 : -OH broad peak exists; 3314cm -1 :-NH- exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1711cm -1 :-C=O weakened; 1698cm -1 : -C=O (coordinated with calcium) exists.
[0111] S23, self-assembly, i.e.
[0112] The material obtained in step S22 is placed in the zwitterionic copolymer solution, heparin calcium solution A, tannic acid solution, and heparin calcium solution B in sequence; wherein each process is allowed to stand for 50 minutes.
[0113] The concentration of the zwitterionic solution is 0.015 g / mL;
[0114] The concentration of the heparin calcium solution A is 0.008 g / mL;
[0115] The concentration of the tannic acid solution is 0.008 g / mL; and
[0116] The concentration of the heparin calcium solution B is 0.015 g / mL.
[0117] Its infrared data is as follows (reflected infrared): 3489cm -1 :-OH broad peak exists and is enhanced; 3314cm -1 :-NH- does not exist; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1711cm -1 :-C=O weakened; 1698cm -1 : -C=O (coordinated with calcium) exists and is enhanced.
[0118] S24, freeze-dried, i.e.
[0119] The substance obtained in step S23 is freeze-dried at -20°C for 24 hours to obtain a hydrogel material for genital plastic surgery.
[0120] Example 2
[0121] The rest is the same as in Example 1, except that:
[0122] A method for preparing a zwitterionic copolymer, wherein in step S11,
[0123] The usage ratio of lactic acid to gallic acid is 0.5 mol:0.5 mol.
[0124] Example 3
[0125] The rest is the same as in Example 1, except that:
[0126] A method for preparing a zwitterionic copolymer, wherein in step S11,
[0127] The usage ratio of lactic acid to gallic acid is 0.3 mol:0.7 mol.
[0128] Example 4
[0129] The rest is the same as in Example 1, except that:
[0130] A method for preparing a zwitterionic copolymer, wherein in step S12,
[0131] The usage ratio of the intermediate product, the zwitterion and N,N-dimethylformamide is 0.5 mol: 0.5 mol: 500 mL.
[0132] Example 5
[0133] The rest is the same as in Example 1, except that:
[0134] A method for preparing a zwitterionic copolymer, wherein in step S12,
[0135] The usage ratio of the intermediate product, the zwitterion and N,N-dimethylformamide is 0.4 mol: 0.6 mol: 500 mL.
[0136] Example 6
[0137] The rest is the same as in Example 1, except that:
[0138] A method for preparing a zwitterionic copolymer comprises the following steps:
[0139] S11, protect from light, add lactic acid, gallic acid, glycidyl methacrylate, inhibitor and tetrabutylammonium bromide to tetrahydrofuran, heat and reflux for 18 hours; cool to room temperature, distill under reduced pressure, take the concentrate and place it under vacuum at 40°C for 12 hours to obtain an intermediate product.
[0140] The lactic acid, gallic acid and glycidyl methacrylate are added in a molar ratio of 1:1 between the total amount of carboxyl groups and the epoxy groups; and
[0141] The dosage ratio of lactic acid to gallic acid is 0.4 mol:0.6 mol;
[0142] The usage ratio of glycidyl methacrylate, tetrabutylammonium bromide and tetrahydrofuran is 0.1 mol: 0.02 mol: 100 mL;
[0143] The dosage of the polymerization inhibitor is 0.2 wt % of glycidyl methacrylate.
[0144] Its infrared data are as follows: 3495cm -1 : -OH broad peak exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1735cm -1 :-C=O exists; 1606cm -1 、811cm -1 :-C=C- exists; 1265cm -1 、893cm -1 、825cm -1 : Epoxy group does not exist.
[0145] S12, adding the intermediate product, 2-methacryloyloxyethyl phosphorylcholine, and photoinitiator 1173 to N,N-dimethylformamide, irradiating under UV lamp for 10 minutes, removing the UV lamp, performing vacuum distillation, adding methanol to the concentrate to produce a precipitate, filtering, taking the precipitate, and vacuum drying at 60°C for 8 hours to obtain a zwitterionic copolymer
[0146] The usage ratio of the intermediate product, 2-methacryloyloxyethyl phosphorylcholine and N,N-dimethylformamide is 0.45 mol: 0.55 mol: 500 mL.
[0147] The amount of the photoinitiator 1173 is 5wt% of the total mass of the reactants;
[0148] The UV light intensity is 600mW / cm 2 .
[0149] Its infrared data are as follows: 3495cm -1 : -OH broad peak exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1735cm -1 :-C=O exists; 1606cm -1 、811cm -1 :-C=C- does not exist; 1187cm -1 :-P=O exists.
[0150] Example 7
[0151] The rest is the same as in Example 1, except that:
[0152] A method for preparing a zwitterionic copolymer comprises the following steps:
[0153] S11, protect from light, add lactic acid, gallic acid, glycidyl methacrylate, inhibitor and tetrabutylammonium bromide to tetrahydrofuran, heat and reflux for 24 hours; cool to room temperature, distill under reduced pressure, take the concentrate and place it under vacuum and dry it at 40°C for 12 hours to obtain an intermediate product.
[0154] The lactic acid, gallic acid and glycidyl methacrylate are added in a molar ratio of 1:1 between the total amount of carboxyl groups and the epoxy groups; and
[0155] The dosage ratio of lactic acid to gallic acid is 0.4 mol:0.6 mol;
[0156] The usage ratio of glycidyl methacrylate, tetrabutylammonium bromide and tetrahydrofuran is 0.1 mol: 0.02 mol: 100 mL;
[0157] The dosage of the polymerization inhibitor is 0.2 wt % of glycidyl methacrylate.
[0158] Its infrared data are as follows: 3495cm -1 : -OH broad peak exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1735cm -1 :-C=O exists; 1606cm -1 、811cm -1 :-C=C- exists; 1265cm -1 、893cm -1 、825cm -1 : Epoxy group does not exist.
[0159] S12, adding the intermediate product, 2-methacryloyloxyethyl phosphorylcholine, and photoinitiator 1173 to N,N-dimethylformamide, irradiating under UV lamp for 50 minutes, removing the UV lamp, performing vacuum distillation, adding methanol to the concentrate to produce a precipitate, filtering, taking the precipitate, and vacuum drying at 60°C for 8 hours to obtain a zwitterionic copolymer
[0160] The usage ratio of the intermediate product, 2-methacryloyloxyethyl phosphorylcholine and N,N-dimethylformamide is 0.4-0.5 mol: 0.5-0.6 mol: 500 mL.
[0161] The amount of the photoinitiator 1173 is 1wt% of the total mass of the reactants;
[0162] The UV light intensity is 200mW / cm 2 .
[0163] Its infrared data are as follows: 3495cm -1 : -OH broad peak exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1735cm -1 :-C=O exists; 1606cm -1 、811cm -1 :-C=C- does not exist; 1187cm -1 :-P=O exists.
[0164] Example 8
[0165] The rest is the same as in Example 1, except that:
[0166] A method for preparing a zwitterionic copolymer, wherein in step S12,
[0167] The 2-methacryloyloxyethyl phosphorylcholine was replaced with methacryloylethyl sulfobetaine.
[0168] Example 9
[0169] The rest is the same as in Example 1, except that:
[0170] A method for preparing a hydrogel material for genital plastic surgery, comprising the following steps:
[0171] S21, preparing the mixed solution and freeze-drying, i.e.
[0172] The mesenchymal stem cell solution was added to the polymer-based mixed solution, mixed evenly and poured into a mold; and freeze-dried at -20°C for 24 hours.
[0173] The polymer-based mixed solution is: a solution with a sodium alginate solution concentration of 0.05 g / mL; a solution with a carboxymethyl chitosan solution concentration of 0.03 g / mL; and a solution with a gelatin solution concentration of 0.05 g / mL; sodium alginate, carboxymethyl chitosan, and gelatin solution are mixed at a volume ratio of 2.0:1.0:1.0 to obtain a polymer-based mixed solution;
[0174] The solute sodium alginate of the sodium alginate solution is prepared by adding high molecular weight sodium alginate and low molecular weight sodium alginate in a mass ratio of 0.6:0.4; and
[0175] The number average molecular weight of the high molecular weight sodium alginate is 150 kDa;
[0176] The number average molecular weight of the low molecular weight sodium alginate is 5 kDa;
[0177] The volume ratio of the mesenchymal stem cell solution to the polymer base mixed solution is 1.0:0.8;
[0178] The concentration of the mesenchymal stem cell solution is 1×10 9 Pieces / mL.
[0179] S22, ionic cross-linking, i.e.
[0180] The substance obtained in step S21 is placed in a calcium chloride solution, allowed to stand for 40 minutes, and excess liquid is removed;
[0181] The concentration of the calcium chloride solution is 0.03 g / mL.
[0182] Its infrared data is as follows: 3486cm -1 : -OH broad peak exists; 3314cm -1 :-NH- exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1711cm -1 :-C=O weakened; 1698cm -1 : -C=O (coordinated with calcium) exists.
[0183] S23, self-assembly, i.e.
[0184] The material obtained in step S22 is placed in the zwitterionic copolymer solution, heparin calcium solution A, tannic acid solution, and heparin calcium solution B in sequence; wherein each process is allowed to stand for 40 minutes.
[0185] The concentration of the zwitterionic solution is 0.02 g / mL;
[0186] The concentration of the heparin calcium solution A is 0.01 g / mL;
[0187] The concentration of the tannic acid solution is 0.01 g / mL; and
[0188] The concentration of the heparin calcium solution B is 0.02 g / mL.
[0189] Its infrared data is as follows (reflected infrared): 3489cm -1 :-OH broad peak exists and is enhanced; 3314cm -1 :-NH- does not exist; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1711cm -1 :-C=O weakened; 1698cm -1: -C=O (coordinated with calcium) exists and is enhanced.
[0190] S24, freeze-dried, i.e.
[0191] The substance obtained in step S23 is freeze-dried at -20°C for 24 hours to obtain a hydrogel material for genital plastic surgery.
[0192] Example 10
[0193] The rest is the same as in Example 1, except that:
[0194] A method for preparing a hydrogel material for genital plastic surgery, comprising the following steps:
[0195] S21, preparing the mixed solution and freeze-drying, i.e.
[0196] The mesenchymal stem cell solution was added to the polymer-based mixed solution, mixed evenly and poured into a mold; and freeze-dried at -20°C for 24 hours.
[0197] The polymer-based mixed solution is: a solution with a sodium alginate solution concentration of 0.02 g / mL; a solution with a carboxymethyl chitosan solution concentration of 0.01 g / mL; and a solution with a gelatin solution concentration of 0.02 g / mL; sodium alginate, carboxymethyl chitosan, and gelatin solution are mixed at a volume ratio of 2.0:1.0:2.0 to obtain a polymer-based mixed solution;
[0198] The solute sodium alginate of the sodium alginate solution is prepared by adding high molecular weight sodium alginate and low molecular weight sodium alginate in a mass ratio of 0.8:0.2; and
[0199] The number average molecular weight of the high molecular weight sodium alginate is 100 kDa;
[0200] The number average molecular weight of the low molecular weight sodium alginate is 10 kDa;
[0201] The volume ratio of the mesenchymal stem cell solution to the polymer base mixed solution is 1.0:1.2;
[0202] The concentration of the mesenchymal stem cell solution is 1×10 10 Pieces / mL.
[0203] S22, ionic cross-linking, i.e.
[0204] The substance obtained in step S21 is placed in a calcium chloride solution, allowed to stand for 30 minutes, and excess liquid is removed;
[0205] The concentration of the calcium chloride solution is 0.01 g / mL.
[0206] Its infrared data is as follows: 3486cm -1: -OH broad peak exists; 3314cm -1 :-NH- exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1711cm -1 :-C=O weakened; 1698cm -1 : -C=O (coordinated with calcium) exists.
[0207] S23, self-assembly, i.e.
[0208] The material obtained in step S22 is placed in the zwitterionic copolymer solution, heparin calcium solution A, tannic acid solution, and heparin calcium solution B in sequence; wherein each process is allowed to stand for 60 minutes.
[0209] The concentration of the zwitterionic solution is 0.01 g / mL;
[0210] The concentration of the heparin calcium solution A is 0.005 g / mL;
[0211] The concentration of the tannic acid solution is 0.005 g / mL; and
[0212] The concentration of the heparin calcium solution B is 0.01 g / mL.
[0213] Its infrared data is as follows (reflected infrared): 3489cm -1 :-OH broad peak exists and is enhanced; 3314cm -1 :-NH- does not exist; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1711cm -1 :-C=O weakened; 1698cm -1 : -C=O (coordinated with calcium) exists and is enhanced.
[0214] S24, freeze-dried, i.e.
[0215] The substance obtained in step S23 is freeze-dried at -20°C for 24 hours to obtain a hydrogel material for genital plastic surgery.
[0216] Embodiment 11
[0217] The rest is the same as in Example 1, except that:
[0218] A method for preparing a hydrogel material for genital plastic surgery, in step S21,
[0219] The sodium alginate, carboxymethyl chitosan and gelatin solution are mixed in a volume ratio of 1.0:1.0:1.0.
[0220] The hydrogel materials for genital plastic surgery in the following comparative examples are compared with Example 1:
[0221] Comparative Example 1
[0222] The rest is the same as in Example 1, except that:
[0223] A method for preparing a hydrogel material for genital plastic surgery, in step S23,
[0224] The material obtained in step S22 is placed in heparin calcium solution A, tannic acid solution and heparin calcium solution B in sequence.
[0225] Comparative Example 2
[0226] The rest is the same as in Example 1, except that:
[0227] A method for preparing a zwitterionic copolymer, wherein in step S12,
[0228] The usage ratio of the intermediate product, 2-methacryloyloxyethyl phosphorylcholine, and N,N-dimethylformamide is 0 mol: 0.55 mol: 500 mL; that is, no intermediate product is added.
[0229] Comparative Example 3
[0230] The rest is the same as in Example 1, except that:
[0231] A method for preparing a zwitterionic copolymer, wherein in step S12,
[0232] The usage ratio of the intermediate product, 2-methacryloyloxyethyl phosphorylcholine, and N,N-dimethylformamide is 0.45 mol: 0 mol: 500 mL; that is, no 2-methacryloyloxyethyl phosphorylcholine is added.
[0233] Comparative Example 4
[0234] The rest is the same as in Example 1, except that:
[0235] A method for preparing a hydrogel material for genital plastic surgery, in step S21,
[0236] The sodium alginate, carboxymethyl chitosan and gelatin solution were mixed in a volume ratio of 1.5:0:1.5; that is, no carboxymethyl chitosan solution was added.
[0237] Comparative Example 5
[0238] The rest is the same as in Example 1, except that:
[0239] A method for preparing a hydrogel material for genital plastic surgery, in step S21,
[0240] The sodium alginate, carboxymethyl chitosan and gelatin solution are mixed in a volume ratio of 1.5:1.0:0; that is, no gelatin solution is added.
[0241] Comparative Example 6
[0242] The rest is the same as in Example 1, except that:
[0243] A method for preparing a hydrogel material for genital plastic surgery, in step S21,
[0244] The solute sodium alginate of the sodium alginate solution is prepared by adding high molecular weight sodium alginate and low molecular weight sodium alginate in a mass ratio of 0.7:0; that is, low molecular weight sodium alginate is not added.
[0245] Comparative Example 7
[0246] The rest is the same as in Example 1, except that:
[0247] A method for preparing a hydrogel material for genital plastic surgery, in step S21,
[0248] The solute sodium alginate of the sodium alginate solution is prepared by adding high molecular weight sodium alginate and low molecular weight sodium alginate in a mass ratio of 0:0.3; that is, high molecular weight sodium alginate is not added.
[0249] Comparative Example 8
[0250] The rest is the same as in Example 1, except that:
[0251] A method for preparing a hydrogel material for genital plastic surgery, in step S21,
[0252] The volume ratio of the mesenchymal stem cell solution to the polymer-based mixed solution is 0:1.0; that is, no mesenchymal stem cell solution is added.
[0253] Comparative Example 9
[0254] The rest is the same as in Example 1, except that:
[0255] A method for preparing a hydrogel material for genital plastic surgery, in step S21,
[0256] No freeze-drying step.
[0257] Comparative Example 10
[0258] The rest is the same as in Example 1, except that:
[0259] A method for preparing a hydrogel material for genital plastic surgery,
[0260] No calcium chloride solution ionic crosslinking step.
[0261] Comparative Example 11
[0262] The rest is the same as in Example 1, except that:
[0263] A method for preparing a hydrogel material for genital plastic surgery, in step S23,
[0264] The material obtained in step S22 is placed in the zwitterionic copolymer solution, the tannic acid solution and the heparin calcium solution B in sequence.
[0265] Comparative Example 12
[0266] The rest is the same as in Example 1, except that:
[0267] A method for preparing a hydrogel material for genital plastic surgery, in step S23,
[0268] The material obtained in step S22 is placed in the zwitterionic copolymer solution, heparin calcium solution A, and heparin calcium solution B in sequence.
[0269] Comparative Example 13
[0270] The rest is the same as in Example 1, except that:
[0271] A method for preparing a hydrogel material for genital plastic surgery, in step S23,
[0272] The material obtained in step S22 is placed in sequence in the zwitterionic copolymer solution, the heparin calcium solution A, and the tannic acid solution.
[0273] Comparative Example 14
[0274] The rest is the same as in Example 1, except that:
[0275] The heparin calcium solution was replaced with heparin sodium solution.
[0276] The physical properties of the hydrogel materials for genital plastic surgery prepared in the examples of the present invention and the comparative examples were measured respectively, and the results are shown in Table 1.
[0277] Table 1 Physical test performance of each embodiment
[0278]
[0279]
[0280] First, it can be seen from Examples 1-11 in Table 1 that the hydrogel material for genital plastic surgery of the present invention has excellent mechanical properties, cell compatibility, plastic surgery and repair effects, antibacterial properties, and the like.
[0281] Second, it can be observed from Example 1 and Comparative Examples 1-3 that the hydrogel material for genital plastic surgery of the present invention uses a homemade zwitterionic copolymer, which has a volume expansion effect and can effectively improve the mechanical properties; at the same time, the quaternary ammonium salt structure also has an excellent synergistic antibacterial effect; the catechol structure has the function of synergistically adsorbing cells and improving the plastic surgery repair effect; from Example 1 and Comparative Examples 4-7, it can be observed that the hydrogel of the present invention uses sodium alginate, carboxymethyl chitosan, and gelatin as main raw materials, wherein sodium alginate has better flexibility when used in a high and low molecular weight compound, carboxymethyl chitosan has excellent antibacterial properties, and gelatin has the function of promoting cell proliferation and differentiation, and the components work synergistically with each other and have excellent mechanical properties. performance and antibacterial and cell proliferation and differentiation promotion; it can be observed from Example 1 and comparative example 8 that stem cells are differentiated and can effectively promote rapid wound healing and function; it can be observed from Example 1 and comparative examples 1, 9-14 that the layer-by-layer self-assembly of zwitterionic copolymer, heparin calcium A, tannic acid, and heparin calcium B has excellent mechanical enhancement effect, while the outer layer of tannic acid and heparin calcium have anti-thrombotic and antibacterial functions, cell adsorption and other functions, which synergistically enhance the rehabilitation effect and effectively reduce the plastic surgery repair cycle; in addition, after freeze-drying and multi-step addition of calcium ions, the cross-linking density is increased, and the mechanical properties are further improved; third, compared with heparin sodium, heparin calcium has better mechanical properties and plastic surgery repair effects.
[0282] In summary, the hydrogel material for genital plastic surgery of the present invention has excellent mechanical properties, plastic surgery and repair effects, antibacterial properties, cell compatibility, and the like.
[0283] The test method is as follows:
[0284] (1) OD value / absorbance: The hydrogel to be tested was placed in a 37°C incubator to promote gel formation, and culture medium was carefully added after 30 min. CCK-8 was used to detect changes in cell proliferation activity on the 3rd day.
[0285] (2) Mechanical properties: The tensile strength of the specimens was tested using a universal mechanical testing machine. The specimen specifications were 10.0 mm in width, 1.0 mm in thickness, and 40 mm in length. The tensile rate was 100 mm / min at room temperature. The test data was the average value of 5 parallel samples.
[0286] (3) Plastic surgery repair cycle: White rabbits were used for testing and verification. Ten white rabbits were randomly selected for each embodiment and their average value was tested. The specific process is as follows:
[0287] A docile New Zealand white rabbit was selected and anesthetized with 3% sodium pentobarbital at a dose of 1 ml / kg. After routine skin preparation, disinfection, and draping, an elastic band was wrapped around the root of the rabbit's corpus cavernosum, and then the elastic band was clamped with an artery clamp. A 5 mm longitudinal incision was made in the right corpus cavernosum, and the hydrogel material to be tested was quickly transplanted to the defect of the corpus cavernosum and sutured. One month after surgery, the repaired male rabbit was placed in the same cage with a normal female rabbit, and the time between the cage and the date of the newborn rabbit was recorded.
[0288] (4) Antibacterial activity: Referring to GB4789.2-2010 “National Food Safety Standard - Determination of Total Colony Count for Food Microbiological Examination”, the antibacterial and antimicrobial activity test of Escherichia coli was conducted.
[0289] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a zwitterionic copolymer, characterized in that: The following steps are involved: S11, subjecting lactic acid, carboxylated catechol derivative and epoxy acrylate to a ring-opening reaction to obtain an intermediate product; S12, subjecting the intermediate product and zwitterion to free radical polymerization to obtain a target product, namely a zwitterionic copolymer.
2. The preparation method according to claim 1, characterized in that: The lactic acid, carboxylated catechol derivative and epoxy acrylate are added in a molar ratio of the total amount of carboxyl groups to the epoxy groups of 1:1; and The usage ratio of the lactic acid and the carboxylated catechol derivative is 0.3-0.5 mol: 0.5-0.7 mol.
3. The preparation method according to claim 1, characterized in that: The ratio of the intermediate product to the zwitterion is 0.4-0.5 mol: 0.5-0.6 mol; and, The zwitterion contains an acryloyloxy structure.
4. A zwitterionic copolymer, characterized in that Prepared by the preparation method according to any one of claims 1 to 3.
5. A method for preparing a hydrogel material for genital plastic surgery, characterized in that: The following steps are involved: S21, preparing the mixed solution and freeze-drying, i.e. Add mesenchymal stem cell solution to the polymer base mixed solution, mix well and pour into a mold; freeze-dry; S22, ionic cross-linking, i.e. The substance obtained in step S21 is placed in a calcium chloride solution, allowed to stand for 30-40 minutes, and excess liquid is removed; S23, self-assembly, i.e. The material obtained in step S22 is placed in a zwitterionic copolymer solution, a heparin calcium solution A, a tannic acid solution, and a heparin calcium solution B in sequence; Each process is left to stand for 40-60 minutes; S24, freeze-dried, i.e. The material obtained in step S23 is freeze-dried to obtain a hydrogel material for genital plastic surgery.
6. The preparation method according to claim 5, characterized in that: The polymer-based mixed solution is a mixture of sodium alginate solution, carboxymethyl chitosan solution and gelatin solution in a volume ratio of 1.0-2.0:1.0:1.0-2.0; and The concentration of the sodium alginate solution is 0.02-0.05 g / mL; The concentration of the carboxymethyl chitosan solution is 0.01-0.03 g / mL; The concentration of the gelatin solution is 0.02-0.05 g / mL.
7. The preparation method according to claim 6, characterized in that: The solute sodium alginate of the sodium alginate solution is prepared by adding high molecular weight sodium alginate and low molecular weight sodium alginate in a mass ratio of 0.6-0.8:0.2-0.4; and The number average molecular weight of the high molecular weight sodium alginate is 100-150 kDa; The number average molecular weight of the low molecular weight sodium alginate is 5-10 kDa.
8. The preparation method according to claim 5 or 6, characterized in that: The volume ratio of the mesenchymal stem cell solution to the polymer base mixed solution is 1.0:0.8-1.2; the concentration of the mesenchymal stem cell solution is 10 9 -10 10 Pieces / mL.
9. The preparation method according to claim 5, characterized in that: The concentration of the calcium chloride solution is 0.01-0.03 g / mL.
10. The preparation method according to claim 5, characterized in that: The concentration of the zwitterionic solution is 0.01-0.02 g / mL; The concentration of the heparin calcium solution A is 0.005-0.01 g / mL; The concentration of the tannic acid solution is 0.005-0.01 g / mL; and The concentration of the heparin calcium solution B is 0.01-0.02 g / mL.
Citation Information
Patent Citations
Antibacterial compound hydrogel and preparation method thereof
CN111150880A
Hydrogel rich in exosome as well as preparation method and application thereof
CN115581810A
Composite hydrogel loaded with nano antibacterial material as well as preparation method and application of composite hydrogel
CN117618638A
Preparation method and application of novel exosome hydrogel
CN117942295A
